The Use of Rocuronium With Suggammadex in Electroconvulsive Therapy of the Patient With Neuroleptic Malignant Syndrome: Case Report (Annals of Medical Research, 2021)
None
Keywords: Neuroleptic Malignant Syndrome; Electroconvulsive Therapy; Malignant Hyperthermia; Suggammadex.